Community forestry for environmental sustainability and ecotourism: the context and problems in Indonesia. Issue 1 (1st June 2022) - Sulistiowati, R; Wahyuni, S; Yunanto, M K; Elsera, M; Yudiatmaja, W E; Samnuzulsari, T
Abstract: Social forestry is one of the programs delivered by the Indonesian government to distribute forest ownership to society. The program consisted of village forest, customary forest, community forest, a people forest plantation, and partnership for forestry. This study merely focused on the community forest in Indonesia. The purpose of this research is to analyze the context and problems during the implementation process of permit delivery for community forests in Gunungkidul, Yogyakarta, Indonesia. A qualitative method was used in this research to understand the case of community forests in the study site. Data were collected using an interview, non-participant observation, and secondary document. We find that many groups of farmers have not received the permit for forestry management because of regulatory constraints. The problems are induced by many policies in the forestry sector regulating various forms of forest management permits contradicting the principle of the decentralized forest management policy. We recommend to the government to simplify the process of forest permit management, especially for the community forest.